Research on Large Divergence Angle Laser Ranging System - Junwen Ji; Suhui Yang; Yimin Feng (Photonics)
This study investigates a laser ranging technology scheme featuring a large divergence angle for both the emitted and received laser beams, focusing on applications where both the measured target and the ranging carrier are high-mobility platforms. A dual-concave beam-reducing lens design is adopted to reshape the original beam divergence angle of 10 mrad from the erbium glass laser into a ranging output beam divergence angle of 26 mrad, while maintaining the Gaussian energy distribution of the original laser beam. A φ500 μm photosensitive surface APD detector is used, and a combination of aspherical and spherical elements is employed in the receiving optical system to achieve a 30 mrad large field-of-view echo reception within the small photosensitive surface. This laser ranging system addresses the challenge of aiming and tracking for laser ranging between relatively high-speed moving objects and reduces the stability precision requirements for the ranging carrier platform.